Determinants of Intention to Use Siskeudes: Extended of Decomposed Theory of Planned Behavior Model - Widagdo, Ari Kuncara; Ika, Siti Rochmah; Satria, Sena (Jurnal Akuntansi dan Bisnis, 2020)
This study aims to examine factors that influence interest in using the village fund information system (SISKEUDES) by using extended Decomposed Theory of Planned Behavior Model. The respondents are 301 SISKEUDES operators in the Banyumas District. The hypotheses testing uses Partial Least Square (PLS). The result shows that attitude, subjective norms, perception of behavior control, and perceived human resource quality influence the intention to use SISKEUDES. This study demonstrates the appropriateness of the extended Decomposed Theory of Planned Behavior Model in explaining the acceptance of a mandatory system.Penelitian ini bertujuan untuk menguji faktor-faktor yang memengaruhi minat dalam menggunakan sistem informasi dana desa (SISKEUDES) dengan menggunakan extended Decomposed Theory of Planned Behavior Model. Responden adalah 301 operator SISKEUDES di Kabupaten Banyumas. Pengujian hipotesis menggunakan Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa sikap, norma subyektif, persepsi kontrol perilaku, dan persepsi kualitas sumber daya manusia memengaruhi niat untuk menggunakan SISKEUDES. Studi ini menunjukkan kesesuaian extended Decomposed Theory of Planned Behavior Model dalam menjelaskan penerimaan sistem yang bersifat wajib.